Coronavirus Infection in Children - Leonidovna, Bannova Svetlana; Gennadievich, Puzyrev Viktor (Asian Pacific Journal of Environment and Cancer, 2020)
SARS-COV-2 is a highly contagious anthroponotic infection. The relevance of the study of the disease is due to the wide prevalence of the pandemic worldwide to the extent that it affects all age groups and populations, the lack of long-term and intense immunity, and high mortality, mainly among adults.Children are also susceptible to SARS-COV-2 infection, but this age group is more likely to be asymptomatic. This article summarizes the main trends in clinical manifestations and treatment of coronavirus infection in children available in current moment.